Distance from health facility and mothers’ perception of quality related to skilled delivery service utilization in northern Ethiopia - Fisseha G; Berhane Y; Worku A; Terefe W (Dove Medical Press, 2017)
Girmatsion Fisseha,1 Yemane Berhane,2 Alemayehu Worku,2,3 Wondwossen Terefe1 1Mekelle University, College of Health Science, School of Public Health, Mekelle, Ethiopia; 2Addis Continental Institute of Public Health, Epidemiology Department, Addis Ababa, Ethiopia; 3Addis Ababa University, School of Public Health, Biostatistics Department, Addis Ababa, Ethiopia Background: Poor maternal health service utilization is one of the contributing factors to a high level of maternal and newborn mortality in Ethiopia. The factors associated with utilization of services are believed to differ from one context to another. We assessed the factors associated with skilled delivery service utilization in rural northern Ethiopia.Subjects and methods: A community-based survey was conducted among mothers who gave birth in the 12 months preceding the study period, from January to February 2015, in the Tigray region of Ethiopia. Multistage sampling technique was used to select mothers from the identified clusters. Households within a 10 km radius of the health facility were taken as a cluster for a community survey. Data were collected using face-to-face interview at the household level. We compared the mothers who reported giving birth to the index child in a health facility and those who reported delivering at home, in order to identify the predictors of skilled delivery utilization. Multivariable logistic regression model was used to determine the predictors of skilled delivery service utilization. The results are presented with odds ratio (OR) and 95% confidence interval (CI).Results: A total of 1,796 mothers participated in the study, with a 100% response rate. Distance to health facilities (adjusted odds ratio [AOR] =0.53 [95% CI: 0.39, 0.71]), perception of mothers to the availability of adequate equipment in the delivery service in their catchment area (AOR =1.5 [95% CI: 1.11, 2.13]), experiencing any complication during childbirth, using antenatal care, lower birth order and having an educated partner were the significant predictors of skilled delivery service utilization.Conclusion: Implementing community-based intervention programs that will address the physical accessibility of delivery services, such as the ambulance service, road issues and waiting rooms, and improving quality maternity service will likely reduce the current problem. Keywords: distance from health facility, perception of quality, skilled delivery service utilization, Northern Ethiopia